Celebrating International Museum Day 2023... Internationally - Aija Héloïse Pince (EXARC Journal)
In order to celebrate International Museum Day 2023, I strived to make a change in a personal format to mark the occasion as being as international as possible. Back in the day, when I was working at Dar al-Athar al-Islamiyyah, we marked the day as near as possible. Given that May was going to be too hot for comfort, we usually celebrated a month earlier. I was happy with that, but even then, despite the splendours of the al-Sabah collection that have travelled to so many museums (the Louvre, The Met, the British Museum, the Prado and many others), IMD seemed to end up a very local affair, because while we put on a great show, with a great childrens’ programme as well as other artistic and ecological functions, nobody came to us from around the world.